Convective drying of Butia Capitata pulp: effect of air temperature on kinetic and quality parameters (Research, Society and Development, 2020)
Butiá (Butia capitata) is a typical Brazilian Cerrado fruit, rich in several bioactive compounds. This work aimed to study the influence of air temperature on drying kinetics and quality parameters of butiá pulp. The pulps were dried at 50 and 70 °C. Mathematical models were fitted to the moisture ratio data. The effective moisture diffusivity (Deff) and the drying rate (DR) were calculated. The fresh and dried pulps were characterized in terms of moisture content (MC), water activity (aw), total carotenoids content (TCC), yellow flavonoids, total phenolic content (TPC), antioxidant capacity and color. The Page model was the one that best fitted to the moisture ratio data. Drying reduced MC, aw and the bioactive compounds content and altered colorimetric parameters. The higher temperature resulted in lower TCC and higher total color difference. However, it reduced the drying time (from 300 to 180 min), with higher Deff and DR and resulted in samples with higher retention of yellow flavonoids, TPC and total antioxidants and a lower browning index. Therefore, 70 °C was the most suitable temperature for drying butiá pulp.